Epistemic Exclusion and Marine Resource Governance: The Case of the Bajo Community in Torosiaje, Indonesia - Tamu, Yowan; Sari, Intan Permata; Tahara, Tasrifin; Utina, Ramli; Mahading, Ikha Hardiyanti Puspita (Jurnal Ilmiah Peuradeun, 2025)
This study investigated the exclusion of local ecological knowledge in marine resource governance by examining the case of the Bajo community in Torosiaje, Gorontalo Province, Indonesia. Using a qualitative ethnographic approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings revealed that the exclusion of traditional ecological knowledge was not merely incidental, but it was rooted in structural power asymmetries, institutional neglect, and epistemological bias. This exclusion undermined ecological sustainability, disrupts cultural practices, and weakened the role of Indigenous communities as environmental stewards. By employing the frameworks of Traditional Ecological Knowledge (TEK) and Political Ecology, the study provided a critical analysis of how state-led, technocratic policies marginalize Indigenous knowledge systems. The research contributes to global discourses on ecological justice and inclusive governance by demonstrating the need to re-centre Indigenous epistemologies in environmental decision-making. This study offers a novel perspective by linking epistemic exclusion to the broader challenges of marine policy reform and sustainability in the Global South.